2019
DOI: 10.2138/gselements.15.6.393
|View full text |Cite
|
Sign up to set email alerts
|

Kimberlites from Source to Surface: Insights from Experiments

Abstract: High-pressure experiments are unconvincing in explaining kimberlites as direct melts of carbonated peridotite because the appropriate minerals do not coexist stably at the kimberlite liquidus. High-pressure melts of peridotite with CO2 and H2O have compositions similar to kimberlites only at pressures where conditions are insufficiently oxidizing to stabilize CO2: they do not replicate the high K2O/Na2O of kimberlites. Kimberlite melts may begin their ascent at ≈300 km depth in reduced conditions as melts rich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Recent geochemical fingerprinting of kimberlites revealed that some kimberlite erupted above basal mantle structures could be derived from a primitive, depleted mantle source, whereas kimberlite erupted away from basal mantle structures could be derived from a source that contains deeply subducted crustal material [ 80 ]. Even though upwelling of hot mantle from the deep Earth may provide the source of heat leading to kimberlite eruption, the physical processes that could link basal mantle structures [>2000 km deep; 26] and kimberlite eruption from ~120–300 km depth [ 12 , 13 ] are not yet firmly established.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent geochemical fingerprinting of kimberlites revealed that some kimberlite erupted above basal mantle structures could be derived from a primitive, depleted mantle source, whereas kimberlite erupted away from basal mantle structures could be derived from a source that contains deeply subducted crustal material [ 80 ]. Even though upwelling of hot mantle from the deep Earth may provide the source of heat leading to kimberlite eruption, the physical processes that could link basal mantle structures [>2000 km deep; 26] and kimberlite eruption from ~120–300 km depth [ 12 , 13 ] are not yet firmly established.…”
Section: Discussionmentioning
confidence: 99%
“…Kimberlite eruptions are rapid magmatic events with magma ascending at speeds up to 20 m s -1 [ 9 , 10 ], which is geologically instantaneous compared to average plate motion at ~1.26 × 10 −9 m s -1 (4 cm yr -1 ) over the last 200 Myr [ 11 ]. Kimberlites originate from depths in excess of 120–150 km [ 12 ], forming from melts that may pool from up to ~300 km depth [ 13 ]. Some rare superdeep (sub-lithospheric) kimberlites may have ascended from as deep as 800 km [ 14 17 ], although these diamonds could have been transported to the base of the lithosphere before being entrained by kimberlite magmas [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are some limitations associated with the perovskite and monticellite oxybarometers (Bellis & Canil, 2007; Canil & Bellis, 2007; Le Pioufle and Canil, 2012), the relative differences in f O 2 rather than absolute values are of importance here. Metasomatized mantle lithosphere is considered to be oxidized (e.g., Foley & Fischer, 2017; Foley et al., 2019; Woodland et al., 1996; Yaxley et al., 2017). Therefore it follows, to a first order approximation, that progressive assimilation of enriched SCLM material increases oxidation levels in kimberlite melts.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of sulfates requires prevailing relatively oxidising conditions in the later stage of kimberlite melt crystallisation and/or during subsolidus hydrothermal alteration. Previous work has indeed demonstrated that kimberlite melt oxygen fugacity progressively increases during crystallisation, based on experimental (e.g., Foley et al, 2019) as well as natural evidence, such as decreasing V/Sc in magmatic olivine rims (Giuliani, 2018;Howarth & Taylor, 2016); increasing melt Mg/Fe 2+ during groundmass crystallisation (Bussweiler et al, 2015;Soltys et al, 2018a;Soltys, Giuliani, Phillips, & Kamenetsky, 2020); and increasing Fe 3+ /ΣFe in garnet in peridotite xenoliths in kimberlites occurring shortly before kimberlite emplacement (Hanger et al, 2015). The formation of native Ni and Cu locally associated with other products of sulfide alteration does not contradict this scenario because these phases form under relatively oxidising conditions (i.e., log (fO 2 ) > quartz-fayalite-magnetite buffer).…”
Section: Sulfate-sulfide Isotopic Fractionationmentioning
confidence: 99%